Foot replantation by the autotransplantation type as an alternative to reamputation and prosthesis replacement - E. Yu. Shibayev; P. A. Ivanov; D. A. Kisel (Трансплантология (Москва))
The paper provides a case of foot replantation by the autotransplantation type after train run-over-inflicted injury, by shortening the limb by 12 cm, followed by distraction in the external fixation apparatus. The technical features of the procedure comprising the elements of autotransplantation and up-to-date orthopedic technology of bone elongation are described. A patient’s good rehabilitation is shown to be possible after replantation of a limb in severe injury generally resulting in its loss. The described procedure assures a high reliability and predictability of functional and aesthetic results that cannot be achieved via prosthesis replacement.